Estimation of genetic parameters of reproductive traits in Zandi sheep using linear and threshold models - Mohammadi, H.; Moradi Shahrebabak, M.; Moradi Sharebabak, H.; Vatankhah, M. (Czech Journal of Animal Science, 2012)
Genetic parameters for reproductive traits in Zandi sheep were estimated from data records of 5025 lambs from 178 sires and 1967 dams collected between the years 1993 and 2010 using ASReml statistical package. Genetic parameters were estimated for four basic and two composite traits. Year of lambing and age of ewe were used as fixed effects. Due to repeated record of ewe animal direct genetic effects and permanent environmental effects were considered random. The heritability estimates for conception rate, number of lambs born, number of lambs born alive, number of lambs alive at weaning, number of lambs born per ewe exposed, and number of lambs weaned per ewe exposed were low with linear model - 0.05, 0.14, 0.12, 0.09, 0.05, and 0.04 respectively while the estimates resulting from threshold analysis were 0.11, 0.19, 0.14, 0.16, 0.12, and 0.11, respectively. Estimates of heritabilities for animal genetic and permanent environmental effects were low mainly due to the typical strong influence of environmental factors on reproductive traits. Estimates of repeatabilities for animal permanent environmental effects were low to medium by linear analysis, and medium by threshold analysis. These estimates of genetic parameters may provide a basis for deriving selection indexes for reproductive traits.
Keywords: reproductive traits; genetic parameters; linear model; threshold model; Zandi sheep